1987
DOI: 10.1021/ja00243a016
|View full text |Cite
|
Sign up to set email alerts
|

Spin coupling in metalloporphyrin .pi.-cation radicals

Abstract: IIIS, bond distances; Table IVS, bond angles; listings of magnetic susceptibility data for [Cu(TMP')][SbCl6]-C6H5F and [VO-(TPP')] [SbCl6] (9 pages); listings (X10) of the observed and calculated structure amplitudes of [Cu(TPP')][SbCl6] (13 pages). Ordering information is given on any current masthead page.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
70
0

Year Published

1998
1998
2008
2008

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 100 publications
(77 citation statements)
references
References 2 publications
7
70
0
Order By: Relevance
“…2, i.e., the Cu-N(pyr), Cu-N(an)eq, and Cu-N(an)ax interactions with the N and R values of 1.6 and 2.05 Å, 2.4 and 1.98 Å, and 2.4 and 2.32 Å, respectively, where N(pyr), N(an)eq, and N(an)ax, respectively, denote the coordinating nitrogen atom of H2tpp, AN at the equatorial site, and AN at the axial site. Interestingly, the R value for Cu-N(pyr) in the Cu(II)-SAT complex (Cu(H2tpp)(an)4 2+ ) is larger than that (2.02 Å) of Cu(tpp), [71][72][73][74] while the R value of 1.98 Å for Cu-N(an)eq is alomost identical with that (1.99 Å) of the equatorial site of Cu(an)6 2+ . 75 The longer bond distance of Cu-N(pyr) rather than that of Cu(tpp), in which the Cu 2+ ion is just incorporated into the porphyrin core, is ascribed to the limitation due to the steric geometry of the porphyrin core.…”
Section: ·2 Structure Of Cu(ii)-sat Complex As Determined By Fluoresmentioning
confidence: 91%
“…2, i.e., the Cu-N(pyr), Cu-N(an)eq, and Cu-N(an)ax interactions with the N and R values of 1.6 and 2.05 Å, 2.4 and 1.98 Å, and 2.4 and 2.32 Å, respectively, where N(pyr), N(an)eq, and N(an)ax, respectively, denote the coordinating nitrogen atom of H2tpp, AN at the equatorial site, and AN at the axial site. Interestingly, the R value for Cu-N(pyr) in the Cu(II)-SAT complex (Cu(H2tpp)(an)4 2+ ) is larger than that (2.02 Å) of Cu(tpp), [71][72][73][74] while the R value of 1.98 Å for Cu-N(an)eq is alomost identical with that (1.99 Å) of the equatorial site of Cu(an)6 2+ . 75 The longer bond distance of Cu-N(pyr) rather than that of Cu(tpp), in which the Cu 2+ ion is just incorporated into the porphyrin core, is ascribed to the limitation due to the steric geometry of the porphyrin core.…”
Section: ·2 Structure Of Cu(ii)-sat Complex As Determined By Fluoresmentioning
confidence: 91%
“…Non-planar cores lead to antiferromagnetically coupled systems since only when the porphinato core deviates signi®cantly from D 4h symmetry are the metal d and ligand a 1u or a 2u orbitals not orthogonal and antiferromagnetic coupling can occur. The diamagnetism of [Cu(TPP á )] + [3,13] and the reduced moment of [Fe(TTP á )(Cl)] + [14], both consistent with antiferromagnetic coupling, were the ®rst derivatives that led to this correlation. Subsequently, the paramagnetism of the mononuclear derivative of [Cu(TMP á )] + [17] (planar core) and the diamagnetism of [Cu(OETPP á )] + [7] and [Cu(OETPP á )(Py)] + [8] (saddled cores) fully con®rmed the importance of core symmetry in controlling the nature of the spin coupling.…”
Section: Core Conformation Changes and Ring-ring Interactionsmentioning
confidence: 91%
“…Study of model Co II porphyrins with oxidation properties 4 have shown that depending on the oxidation conditions, an electron can be released from either the metal atom s or the porphyrin ring. 6 In sublimed layers of meso-tetraphenylporphyrinatocobalt(IO (CoTPP) under diminished pressure of NO 2, the metal is oxidized 7 in the first stage to form a five-coordinate extracomplex O2N 9 CoI[ITPP. This work is devoted to spectral studies of consecutive transformations in the sublimed CoTPP layer in the NO 2 atmosphere.…”
mentioning
confidence: 99%